2008
DOI: 10.1073/pnas.0807514106
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule DNA detection with an engineered MspA protein nanopore

Abstract: Nanopores hold great promise as single-molecule analytical devices and biophysical model systems because the ionic current blockades they produce contain information about the identity, concentration, structure, and dynamics of target molecules. The porin MspA of Mycobacterium smegmatis has remarkable stability against environmental stresses and can be rationally modified based on its crystal structure. Further, MspA has a short and narrow channel constriction that is promising for DNA sequencing because it ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
501
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(512 citation statements)
references
References 38 publications
7
501
2
2
Order By: Relevance
“…Wang and colleagues first showed that the direction in which DNA enters the ␣HL pore (5Ј or 3Ј threading) affects the extent of current block (15), an observation supported by the data of Mathé et al (16), and recent studies have shown that the rate of capture of DNA by protein pores is enhanced when the interior surfaces bear a net positive charge (17,18). Under the high applied potentials required for threading, freely moving DNA is translocated through the wild-type (WT) ␣HL pore too quickly for bases to be identified, unless the bases are modified with bulky groups (19).…”
mentioning
confidence: 65%
“…Wang and colleagues first showed that the direction in which DNA enters the ␣HL pore (5Ј or 3Ј threading) affects the extent of current block (15), an observation supported by the data of Mathé et al (16), and recent studies have shown that the rate of capture of DNA by protein pores is enhanced when the interior surfaces bear a net positive charge (17,18). Under the high applied potentials required for threading, freely moving DNA is translocated through the wild-type (WT) ␣HL pore too quickly for bases to be identified, unless the bases are modified with bulky groups (19).…”
mentioning
confidence: 65%
“…Single M2MspA channels were inserted in lipid bilayers in 0.3 M KCl, 10 mM HEPES/KOH (pH 8.00 ± 0.05) at 23°C as previously described (18,22). The channels used for this study had currents between 110 and 120 pA at 180 mV (trans-side positive) upon insertion.…”
Section: Methodsmentioning
confidence: 99%
“…The M2MspA protein (22) used to form single nanopores was prepared in our laboratory. Briefly, the ORF for M2MspA was constructed by overlapping PCR.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to their biological interest they are increasingly relevant to biotechnology, serving as scaffolds for bacterial surface display (2,3) and atomically precise pores for nanopore-based DNA sequencing. Although the suitability of natural β-barrel membrane proteins for biotechnology has been improved by protein engineering (3)(4)(5)(6)(7)(8)(9)(10), the ability to design membrane proteins de novo would deliver tools customized to meet the demands of each application.…”
mentioning
confidence: 99%